Competitiveness, Performance and Factors Behind the Low Foreign Direct Investment Inflow in Bangladesh (Journal of Governance and Development (JGD), 2016)
The underlying purpose of the study is to find out the competitiveness and performance of Bangladesh in attracting FDI and the factors inhibiting FDI inflow in Bangladesh. It is well known that investment is crucial in attaining sound economic growth. The capital requirement can be met by the foreign investment. Unfortunately, Bangladesh is unable to generate sufficient domestic saving to fuel their aspirations for economic growth. Bangladesh has had low rate of GDP growth, savings and investment historically. This represents macro-economic weakness. But the situation is improving with the steady stead growth rate of more than 6% for last couple of years. Saving investment gap of Bangladesh could be fulfilled by the inflow of FDI to achieve the targeted economic growth rate. The recent performance of Asian region coincided with the enhanced investment activity particularly FDI. However, the performances of the South Asian countries especially Bangladesh has not been encouraging compare to countries in East and South East Asia. Bangladesh is giving an attractive package of incentives compare to the FDI receiving Asian countries but its success is little. The sectoral composition of FDI has been changing significantly from primary sector to manufacturing sector. The contribution of FDI in gross domestic capital formation also came last in Bangladesh among the Asian countries. Share of FDI-GDP ratio is also one of lowest in Bangladesh among the Asian countries. The causes responsible for the low FDI in Bangladesh has been identified as historical factors, socio-economic factors, governance factors, political factors and social and cultural factors.